Evaluation of the protective potential of hydroalcoholic extract of Thymus daenensis on acetaminophen-induced nephrotoxicity in rats. Issue 5 (May 2020) - Ansari, Soheila; Azarmehr, Nahid; Barmoudeh, Zahra; Moslemi, Zahra; Ghahremani, Hossein; Mirzaei, Ali; Salehpour, Zeinab; Rabani, Mohammad Reza; Doustimotlagh, Amir Hossein
Abstract: Background: Acetaminophen (APAP) is an antinociceptive and antipyretic drug that can be useful in therapeutic doses, although it can cause serious damage to the kidney if used overdose. The current study aimed to evaluate the protective effect of Thymus daenensis (TD) extract on APAP-induced kidney damage in rats. Methods: Thirty female Wistar rats were randomly divided into 5 groups: control, APAP (3 g/kg), TD (500 mg/kg), APAP + TD (500 mg/kg), and APAP + N- acetylcysteine (140 mg/kg). The APAP groups received APAP on the 6th day and the rats were sacrificed on the 7th day. Plasma levels of creatinine (Cr) and urea were measured. Ferric reducing antioxidant power (FRAP), nitric oxide (NO) metabolite, total thiol (T-SH), tumor necrosis factor-α (TNF-α) and antioxidant enzymes activity of superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT) were measured in kidney tissue. The gene expression of TNF-α was also measured by real-time PCR. The histological examination of kidney tissue was also performed. Results: Results showed that urea, Cr and FRAP markers markedly elevated in the APAP rats compared with the control group. There was a significant decrease in T-SH levels in the APAP animals in comparison with the control group. CAT activity also augmented in the APAP group compared to the control group. Urea and Cr levels were significantly decreased in the APAP + TD group in comparison with the APAP group. The administration of TD extract significantly increased the SOD enzyme activity. Histological findings were improved in the group treated with TD extract. Conclusion: In general, the results indicate that TD extract can protect against APAP-induced nephrotoxicity by improving biochemical, histological and antioxidant effects. However, more studies are required to determine the mechanism of this extract. Abstract : Thymus daenensis; Acetaminophen; Nephrotoxicity; Oxidative stress; Nephroprotective; Cell biology; Biochemistry; Molecular biology; Toxicology; Zoology